A case of cytomegalovirus-negative Ménétrier's disease with eosinophilia in a child - Keun Hyung Son; Jeong Ja Kwak; Jae Ock Park (Korean Journal of Pediatrics, 2012)
Ménétrier's disease is a rare form of acquired gastropathy characterized by giant rugal folds in the stomach and protein-losing gastropathy. Children with Ménétrier's disease tend to follow a benign self-limited course with symptoms typically completely resolving within 2 to 10 weeks in contrast to the chronic course in adults. A 9-year-old girl presented with a history of gradually worsening abdominal distension, increasing body weight, and abdominal pain for 2 weeks. Physical examination on admission indicated periorbital swelling, pitting edema in both the legs, and abdominal distension with mild diffuse tenderness and shifting dullness. Laboratory tests on admission showed hypoalbuminemia, hypoproteinemia, and peripheral eosinophilia. The test result for anticytomegalovirus immunoglobulin M was negative. Increased fecal alpha 1 anti-trypsin excretion was observed. Radiological findings showed massive ascites and pleural effusion in both the lungs. On gastroscopy, large gastric folds, erythema, erosion, and exudation were noted in the body and fundus of the stomach. Microscopic findings showed infiltration of eosinophils and neutrophils in the gastric mucosa. Her symptoms improved with conservative treatment from day 7 of hospitalization and resolved completely.